In Vitro and In Vivo Electrochemical Measurement of Reactive Oxygen Species After Treatment with Anticancer Drugs - Vaneev, Alexander N.; Gorelkin, Petr V.; Garanina, Anastasiia S.; Lopatukhina, Helena V.; Vodopyanov, Stepan S.; Alova, Anna V.; Ryabaya, Oxana O.; Akasov, Roman A.; Zhang, Yanjun; Novak, Pavel; Salikhov, Sergey V.; Abakumov, Maxim A.; et al. (Analytical chemistry (Washington), 2020)
monitoring of reactive oxygen species (ROS) in tumors during treatment with anticancer therapy is important for understanding the mechanism of action and in the design of new anticancer drugs. In this work, a platinized nanoelectrode is placed into a single cell for detection of the ROS signal, and drug-induced ROS production is then recorded. The main advantages of this method are the short incubation time with the drug and its high sensitivity which allows the detection of low intracellular ROS concentrations. We have shown that our new method can measure the ROS response to chemotherapy in tumor-bearing mice in real-time. ROS levels were measured inside the tumor at different depths in response to doxorubicin. This work provides an effective new approach for the measurement of intracellular ROS by platinized nanoelectrodes.